Catalytic N‐Acylation of Cyclic Amines by Arylglyoxylic Acids via Radical‐Radical Cross‐Coupling. Issue 15 (17th April 2021) - Rahaman, Ajijur; Kumar Singh, Anupam; Gupta, Aniket; Bhadra, Sukalyan
Abstract: A methodical mechanistic investigation allowed for the catalytic N‐acylation of secondary cyclic amine counterparts by arylglyoxylic acids through radical‐radical coupling. The reaction proceeds via a twofold SET‐promoted Cu(I)/Cu(II) catalytic cycle under mild conditions. An analogous reaction variant allows for the N‐acylation in a one‐pot fashion directly starting from a secondary cyclic amine even in the presence of a second amine or hydroxy group. Abstract : A unique copper‐based catalyst system allows for the N‐acylation of cyclic amines by arylglyoxylic acids via radical‐radical cross‐coupling strategy. As evidenced by EPR, UV‐Vis, and mass spectrometric analysis, the amide linkage formation proceeds through a Cu(I)/Cu(II) catalytic cycle involving a twofold SET process.